Evolution of Gi-Fi and Li-Fi in Wireless Networks - Sowbhagya, MP; Vikas Krishna, P; Darshan, S; Nikhil, AR (International Journal of Computer Sciences and Engineering, 2025)
Wireless communication is the transfer of information over a distance without the use of wires. Wireless operations permit services, such as long-range communications that are impossible or impractical to implement using wires. Wireless communication brings fundamental changes to data networking and telecommunications, and makes integrated networks a reality. Network architecture for personal communication systems, wireless LANs, radio, tactical and other wireless networks, and design and analysis of protocols are addressed on a regular basis. At present, the major application of Wi-Fi implementation in libraries is limited to information management. This paper elaborates on new and upcoming technology like Gi-Fi and Li-Fi.